Inflammatory proteins as acute biomarkers of post-traumatic epilepsy - Sødal, Hild Flatmark; Balosso, Silvia; Vezzani, Annamaria; Pasetto, Laura; Bonetto, Valentina; Columbro, Stefano Fabrizio; McCarter, Robert; Helseth, Eirik; Taubøll, Erik; Klein, Pavel (Frontiers in Neurology, 2025)
ObjectiveTo evaluate the potential of targeted inflammatory proteins high mobility group box 1 (HMGB1), matrix metalloproteinase 9 (MMP-9) and interleukins (IL)-6, IL-8 and IL-10 as early biomarkers for post-traumatic epilepsy (PTE) prediction.MethodsIn this prospective, international study, adult patients with traumatic brain injury (TBI) and an anticipated high risk of PTE based on radiological and clinical findings were recruited from Level 1 trauma centers in the USA and Europe. Blood was collected on days 2 and 4 post-TBI. Patients were followed clinically for 24 months for PTE development. Serum levels of the inflammatory markers were assessed using commercially available ELISA and AlphaLISA kits and compared between patients who did and did not develop PTE, and between PTE and a subgroup of non-PTE patients matched for age, sex, and Glasgow Coma Scale using non-parametric tests.ResultsWe found no statistically significant differences in serum levels of the inflammatory markers between PTE patients (n = 13) and non-PTE patients (n = 73), neither at each timepoint nor in the change from day 2 to day 4. Exploring temporal changes within each group, we found a significant decrease in IL-6 level between the two timepoints in the total and matched non-PTE groups, but not in the PTE group. MMP-9 level decreased in both the PTE and the matched non-PTE groups, but not in the total non-PTE group.SignificanceBased on our findings, serum levels of HMGB1, MMP-9, IL-6, IL-8 and IL-10 measured at early time points after TBI may not serve as sensitive biomarkers of PTE. However, a faster decline in IL-6 levels in the non-PTE groups suggests a more rapid resolution of inflammation among patients who do not develop PTE, supporting the role of neuroinflammatory mechanisms in epileptogenesis. The potential of IL-6’s temporal profile as a biomarker of PTE warrants further exploration.